Positive association between different triglyceride glucose index-related indicators and psoriasis: evidence from NHANES - Huang, Dawei; Ma, Rui; Zhong, Xiaoyuan; Jiang, Yuxiong; Lu, Jiajing; Li, Ying; Shi, Yuling (Frontiers in Immunology, 2023)
Background: Psoriasis is a chronic inflammatory skin disease with effects that extend beyond the skin. Insulin resistance (IR) has been associated with psoriasis, but it remains unclear how indicators related to the triglyceride glucose (TyG) index, which were associate with IR, are associated with the condition.The purpose of this study was to investigate the association between psoriasis and three TyG-related indicators: triglyceride glucose-body mass index (TyG-BMI), triglyceride glucose-waist to height ratio (TyG-WHtR), and triglyceride glucose-waist circumference (TyG-WC).